Habitat specificity analyses reveal the importance of grazing refugia for plant diversity conservation in a warm‐temperate grassy ecosystem. Issue 4 (6th September 2016) - Schultz, Nick L.; Reid, Nick; Lodge, Greg; Hunter, John T.
Abstract: Aims: The effects of pastoralism on grassy vegetation are predicted to vary across spatial scales. However, local‐scale effects have generally been better considered than large‐scale effects that may be pertinent for plant diversity conservation. We examined variation in plant diversity in an agricultural region by comparing patterns observed at large and local scales for different land uses. We tested whether habitat specificity (which relates to how specific different species are to particular land uses) can indicate the importance of land uses to plant diversity conservation. Location: Northwest Slopes of New South Wales, Australia. Methods: We surveyed 127 quadrats of grassy vegetation across four land uses: previously cultivated and never‐cultivated native pastures, grazed woodland and ungrazed woodlands (grazing refugia). We assessed (1) species density at the quadrat scale, (2) correlations among explanatory variables and species composition using ordination techniques, and (3) habitat specificity at the regional scale using the γ‐diversity contribution index. Results: At the quadrat scale, differences in species density among land uses were not pronounced. In contrast, habitat specificity was highest in ungrazed, unfertilized woodlands. Land uses that were grazed, cleared of trees and fertilized were generally species dense at the quadrat scale (>40 species 400 m −2 ), but were comprised of a limited suite of native and exotic grasses and forbs, with relatively homogeneous composition across the region. Conclusions: In the region studied, grazing refugia with no tree clearing or history of fertilizer application were valuable for conserving a large number of native species, and so should be protected. Such land uses are currently rare in the region. Simple measures of native or total species density were insufficient for evaluating conservation value, as they did not distinguish habitats with large numbers of common, generalist native species from those with species that were rare or restricted in the region. Analyses of habitat specificity may potentially overcome the pitfalls of basing conservation management decisions on local‐scale measures. Our results also highlighted a need to understand the processes associated with management practices that serve to reduce species diversity at landscape and regional scales. Abstract : Local‐scale measures of plant species density are insufficient for evaluating conservation value, as land uses with similar species density at local scales can make markedly different contributions to larger‐scale diversity. We demonstrate this using habitat specificity analyses to compare pastures, woodlands grazed by livestock, and ungrazed woodlands in an agricultural landscape in eastern Australia.